It's a family affair: How social identification influences family CEO compensation. (5th May 2021) - Mueller, Elisabeth F.; Flickinger, Miriam
Abstract: Research Question/Issue: This study analyzes the heterogeneity of CEO compensation in family firms. Specifically, we investigate the relationship between a family CEO's social identification with the family firm and the level of her or his compensation. Research Findings/Insights: Using a sample of S&P 500 family firms between 2006 and 2014, we find that levels of social identification among family CEOs explain the heterogeneous patterns of CEO compensation among family firms. Our results show that the level of social identification varies among family CEOs. Theoretical/Academic Implications: Our findings indicate that differences in social identification among individual family executives are an important factor in CEO compensation in family firms. This factor has been overlooked in the literature, which has instead focused on the explanatory power of faultlines between family versus non‐family firms or family versus non‐family executives in family firms. Practitioner/Policy Implications: Practitioners may value our finding that socio‐psychological dynamics influence strategic decision‐making in family firms, such as setting the compensation of the family CEO. In particular, practitioners should be aware of each family CEO's level of identification and should not assume that all family members equally socially identify with the family firm.